Cutaneous extracellular matrix - Fujiwara, Hironobu (Henry Stewart Talks, 2014)
Cell-extracellular matrix (ECM) interactions, Skin ECM heterogeneity, ECM-integrin interactions in epidermal stem cell regulation, Non-cell-autonomous functions of the skin ECM, Role of the ECM in ageing and pathological conditions